Gender Matters: Workplace Bullying, Gender, and Mental Health - Rosander, Michael; Salin, Denise; Viita, Lina; Blomberg, Stefan (Frontiers in Psychology, 2020)
The aim of this study was to examine the role of gender in the process of workplace bullying. In particular, we examined how gender affects reported prevalence rates and health consequences of bullying. In addition, we pay particular attention to if the measurement method – self-labelling or behavioural experience methods – affects potential gender differences. A longitudinal study, with two measurement points 18 months apart, was conducted in Sweden (n=1854 at T1; n=1096 at T2). It was a probability sample out of a population of all 3.3 million people in Sweden working at workplaces with ten or more employees. The results showed a slightly higher tendency for women to self-label as bullied (8% vs 6%), while a higher proportion of men than women could be labelled as bullied based on the negative acts they had been exposed to (21% vs 14%). Exposure to negative acts was associated with more subsequent mental health problems for both men and women, whereas self-labelling was associated with mental health problems for men only. Mental health problems at baseline also increased the risk of bullying for both men and women; however, the measurement method affected if the effect was stronger for men or women. Overall, the study advances our understanding of the role of gender in bullying, in particular highlighting the importance of the measurement method for understanding such gender differences.